The Effect of Innovation Ability and Green Innovation on Business Performance Moderated by Competitive Advantage - Stani Sahala Pauziah; Popy Rufaidah (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Indonesia’s property sector grapples with fierce competition and rising expectations for sustainable practices, making it tough for housing developers to boost business performance. Developers must sharpen innovation skills and embrace green approaches to stay ahead. This study investigates how innovation capability and green innovation affect business performance among housing developers under Real Estate Indonesia’s West Java branch, with competitive advantage acting as a potential moderator. Using a quantitative explanatory design, data came from online questionnaires completed by 144 purposively selected managers. Partial Least Squares–Structural Equation Modeling analyzed the responses via SmartPLS. Results show that innovation capability significantly and positively drives business performance. Green innovation has a positive yet insignificant impact. Competitive advantage strongly and directly enhances performance. However, it does not meaningfully moderate the links from innovation capability or green innovation to performance. Superior performance hinges mainly on strong internal innovation and a solid competitive edge. Green initiatives need deeper strategic embedding to unlock their full potential. These insights equip West Java developers with clearer paths to craft smarter innovation strategies and build lasting advantages in a demanding market.